The existence of Islamic Libraries in the Classical Century in Eastern and Western States & the Role of Libraries in the Era of Islamic Civilization: A Case Study of Baghdad (Daula Abbasiyah) and Spanish (Bani Umaiyyah II) - Ulul Absor (Institut Agama Islam Negeri Salatiga, 2017)
Islamic library has been exist in the classical era, precisely during the reign of Umayyad dynasty. The type of library in this era is private library and owned by Khalid Ibnu Yazaid, a semi-public library owned by Khalifah and official, the public libraries is mosque library. The civilization is the result of a genius nation’s. This has been generally recognized. Islamic civilization is the result of Muslims, as well as Western civilization which now shows its glory as well as the result of Western genius. The genius of a nation does not seem to be born and developed without support, hard effort and adequate means, one of the most important tools in this regard is the library. The establishment of the library is a re actualization the awareness of Islamic scientist in improving the intellectual potential of Muslims, especially among students and observers of science. This article tries to explain about the relevance of Islamic library development in classical century, the causal development of Islamic literature between East and West and the role of libraries in the delivery of information.